Comparison of RF and Pulsed Magnetron Sputtering for the Deposition of AZO Thin Films on PET - Oliveira, L. P. G. [UNESP]; Ramos, R. [UNESP]; Rabelo, W. H. [UNESP]; Rangel, E. C. [UNESP]; Durrant, Steven F. [UNESP]; Bortoleto, J. R. R. [UNESP] (Univ Fed Sao Carlos, Dept Engenharia Materials, 2020)
AZO thin films (around 200 nm thick) were grown on polyethylene terephthalate (PET) at room temperature. The plasma was activated using a 13.56 MHz (RF) or a 15 kHz pulsed (PMS) source at a power of 60 W. Optical reflection and transmittance were measured using a UV-Vis-NIR spectrometer over the wavelengths from 190 nm to 2500 nm. All samples show average transmittances greater than 83% in the visible region. The electrical resistivity was measured by the linear four-point probe method to be around 0.001 Omega cm for 200 nm-thick AZO films grown by PMS. XRD results indicated that the films had a hexagonal wurtzite structure and were preferentially oriented in the (002) plane. The surface morphology of the AZO thin films was characterized using Scanning Electron Microscopy (SEM); film chemical composition was studied using Energy Dispersive X-ray Spectroscopy (EDS). For this, an EDS coupled to the Scanning Electron Microscope was used. Only for films grown by PMS were no cracks observed.
Keywords: TCO; zinc oxide; PET; magnetron sputtering